Estudo de trafegabilidade aplicado a veículos de roda em transporte e tração - Knob, Marcelino João (2010)
The ability of vehicles to traverse soft soils is an important aspect of their performance. The geological, climate and topography diversity originated, in Rio Grande do Sul, extensive areas of hydromorphic clay soils, as example, Planssoils and Gleissoils. When saturated of water, these soft soils present low loads support, difficult agricultural machinery work and limit the traverse of military wheeled vehicles. The aim of this study was to determine the limit of soil conditions for trafficability of military 6 x 6 wheeled trucks (Cascavel and Urutu), determine the ground pressure and predict the mobility condition from soil cone index (SCI) and vehicle characteristics. This study also proposed to evaluate the performance of a four wheel drive tractor in drawbar pull test and trafficability performance, to correlate the reduced tire inflation pressure and vehicle loading effect on slipping, drawbar pull, fuel consumption and mobility under different soil moisture conditions. It was found that the Cascavel military truck had a minimal ground pressure of 357 kPa and it needed SCI of 402 kPa in the critical layer for a single pass. The Urutu truck had a ground pressure of 401 kPa and required at least 431 kPa in SCI for one-way pass. The NATO Reference Mobility Model (NRMM) and Mean Maximum Pressure (MPP) predicting model underestimate the soil cone index required for these military vehicles to traverse soft-soils, however, MMP was more appropriate to predict the correct SIC for the tested vehicles. For the tractor experiment it was found that tire inflation pressure changed the ground pressure and the vehicle loading didn t change the ground surface pressure. The greatest drawbar pull were obtained at low tractor speed, reduced inflation pressure and high loading level, operating on hard ground. The lowest specific fuel consumption was obtained on hard ground, empty weight, low tire pressure and operating in high speed gear. The increase of soil moisture decreased the dynamic traction coefficient from 0.57 to 0.31 and the traction efficiency decrease from 50 to 37%. Reduced inflation tire pressure had positive effects on tractor mobility in waterlogged soils, reducing slipping and increasing traverse speed. Using height loading level had negative effect on wet soils because it require more engine power and increase the fuel consumption.